A novel virulent core genome multilocus sequence type CT 11424 of Listeria monocytogenes isolate causing stillbirth in Bangladesh - Muntasir Alam; Md Saiful Islam; M. Ishrat Jahan; Arpita Shyama Deb; Afruna Rahman; Zahidul Islam; Atique Iqbal Chowdhury; Kazi Munisul Islam; Mohammad Zahid Hossain; Dilruba Ahmed; Shams El Arifeen; Emily S. Gurley; et al. (BMC Microbiology)
Abstract Background Listeria monocytogenes is a foodborne pathogen that can lead to severe pregnancy outcomes. This study reports the clinical and genomic characteristics of a Listeria-mediated stillbirth identified in January 2022 through the Child Health and Mortality Prevention Surveillance (CHAMPS) project in Bangladesh. The Lm-BD-CHAMPS-01 isolate was recovered from the blood and cerebrospinal fluid (CSF) of a male stillborn. Maternal history, clinical, and demographic data were collected by the CHAMPS surveillance platform. An expert panel evaluated all reports to determine the role of L. monocytogenes infection in the causal chain of stillbirth. Genomic characterization included multilocus sequence typing (MLST), core genome MLST (cgMLST), serotyping, and the presence or absence of virulence genes. Genetic divergence and phylogenetic analyses were conducted to determine the relationship with other reported isolates globally. Results The isolate Lm-BD-CHAMPS-01 was identified as a novel cgMLST CT11424. It belonged to ST 308, Serotype 4b, Clonal Complex 1, and Phylogenetic Lineage 1. Key L. monocytogenes virulence genes facilitating the crossing of the placental barrier, including full-length inlA, LIPI-1, and LIPI-3, were detected. The isolate was closely related to clinical L. monocytogenes isolates, as determined by GrapeTree based on cgMLST. SNP-based phylogenetic analysis found Lm-BD-CHAMPS-01 to be the most distant from other CC1 isolates in the database. Possible sources of infection included the consumption of contaminated raw vegetables or exposure to pigeons. Conclusions This is the first genome sequence of clinical L. monocytogenes from Bangladesh, which also caused stillbirth. Rural healthcare professionals should be aware of L. monocytogenes infection risks during pregnancy. Pregnant women should be counseled on the dangers of exposure to animals or birds and consumption of potentially contaminated raw food to prevent adverse pregnancy outcomes due to L. monocytogenes infection.